Refugees and asylum seekers in Europe - Schouler-Ocak, M.; Kastrup, M. C. (Die Psychiatrie, 2015)
Background: European countries are the main receiving countries of immigrants such as refugees and asylum seekers belonging to ethnic minority groups due to a global increase in social and political instability as well as socio-economic conflicts. Both the number of ethnic minority groups and the number of people with mental disorders are therefore growing significantly. The current healthcare services are not prepared for this specific population of mentally ill immigrants or ethnic minority groups. Mental health care for immigrant patients is lacking in cultural competence and legislation related to access to and utilisation of health services varies from country to country. Aim: This article attempts to give an overview of the current mental health situation of ethnic minority groups, especially refugees and asylum seekers, in Europe.
Keywords: Ethnic minority groups; refugee and asylum seeker; mental disorders; mental health services; legislation